2019
DOI: 10.1002/bit.27142
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrical stimulation enhances osteogenesis by inducing Bmp2 and Spp1 expressions from macrophages and preosteoblasts

Abstract: The capability of electrical stimulation (ES) in promoting bone regeneration has already been addressed in clinical studies. However, its mechanism is still being investigated and discussed. This study aims to investigate the responses of macrophages (J774A.1) and preosteoblasts (MC3T3‐E1) to ES and the faradic by‐products from ES. It is found that pH of the culture media was not significantly changed, whereas the average hydrogen peroxide concentration was increased by 3.6 and 5.4 µM after 1 and 2 hr of ES, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 89 publications
4
74
0
Order By: Relevance
“…Numerous studies have demonstrated that MAPK pathways and the subsequent signaling cascades of ERK1,2, JHK, and p38 are activated by moderate levels of ROS [86]. Proliferation and differentiation of MSC were shown to be mediated by a mild rise in hypoxia-induced ROS [87][88][89].…”
Section: Estim-induced Cell Response-mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that MAPK pathways and the subsequent signaling cascades of ERK1,2, JHK, and p38 are activated by moderate levels of ROS [86]. Proliferation and differentiation of MSC were shown to be mediated by a mild rise in hypoxia-induced ROS [87][88][89].…”
Section: Estim-induced Cell Response-mechanismsmentioning
confidence: 99%
“…Moreover, EStim was shown to significantly enhance macrophage phagocytic uptake and to selectively modulate cytokine production [116]. EStim's effect of upregulating osteogenic gene (Spp2 and Bmp2) transcription in macrophages could help explain its role in stimulating osteogenesis [89]. In vivo, low-voltage EStim was shown to modify macrophage response by changing the M1 to M2 macrophage ratio [97].…”
Section: Inflammationmentioning
confidence: 99%
“…Moreover, ES has been studied as a potential tool in tissue regeneration to increase the proliferation and differentiation of human stem cells [5,[9][10][11][12][13]. There are several reports in the literature on the use of ES for fracture treatments and tissue repairs using electrical stimulation methodologies, particularly DC or electromagnetic fields [14]. It was established that by applying an electric field (EF), cellular behavior can be modified, including the orientation, proliferation, and rate and direction of cell migration of the corneal, epithelial, and vascular cells, among others [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been reported that the mineralization of rat bone marrow stromal cells may only be improved when ES is applied at early stage of osteo-differentiation [33]. However, Srirussamee et al have applied ES to pre-osteoblasts (MC3T3-E1), and their results showed that the level of Runx2 expression remains unchanged during the early stage [27]. Because pre-osteoblasts are committed cells, their results implied that ES may mainly promote stem cell differentiation to therefore accelerate mineralization.…”
Section: Discussionmentioning
confidence: 98%
“…Although the insertion of electrodes to culture medium may easily provide DCEF treatment, this method may elicit unwanted redox reactions of the medium ingredients as well as the faradaic reaction and corrosion of the electrodes [27]. Therefore, we have previously fabricated a conductive polypyrrole (PPy) film to construct an ES device [28].…”
Section: Introductionmentioning
confidence: 99%